The Effect Of Working Capital Turnover On Profitability In Property And Real Estate Companies Listed On The Indonesia Stock Exchange - Anita Miralda Sinaga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2023)
This study aims to determine the effect of working capital turnover on profitability in property and real estate companies listed on the Indonesian Stock Exchange. The sampling technique used is purposive sampling. The samples are 24 companies, so the research data analyzed are 48. Data analysis techniques used used are descriptive statistics, classical assumption test, and multiple linear regression analysis. The results of the multiple linear regression test have a value of Y= -1.596+0.246X. The results of the partial t test indicate that working capital turnover has no effect. The value of ???????????????????????? (1.543) < ???????????????????????? (2.014) with a significant value (0.130 > 0 ,05) .